Field report PAC 671: Wezmart International Berhad / Nur Haslinda Mustafa Kamal - Mustafa Kamal, Nur Haslinda (Universiti Teknologi MARA, Terengganu, 2024)
Wezmart International Berhad, a pioneering firm based in South East Asia, specializes in Corporate Advisory and Regulatory Technology (A-RegTech) services. The company supports subsidiaries across various compliance domains including Intellectual Property, Company Secretarial, Human Resources, and Accounting Shared Services. Wezmart International Berhad's branch, FS Wong & Co., is situated in Taman Miharja, Cheras, and is responsible for audit assurance services, known for its stringent adherence to international auditing standards and commitment to transparency. Wezmart International Berhad internships offer invaluable experience through hands-on application in audit fieldwork. The intern worked on substantive testing, analytical processes, and control tests under the supervision of FS Wong & Co.'s seasoned auditors. Through this practical approach, they gained a deeper understanding of audit procedures and gained the confidence to successfully navigate intricate financial environments. The internship program offered RM1,000 in allowance money in addition to practical skills. This stipend demonstrated the company's dedication to supporting the professional growth of its interns.